2019
DOI: 10.1002/ijc.32534
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological risk factors for adrenocortical carcinoma: A hospital‐based case–control study

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy whose risk factors are unclear. We explored the association of ACC risk with exposure to selected environmental factors, with a focus on cigarette smoking. We conducted a hospital‐based case–control study at The University of Texas MD Anderson Cancer Center. Cases (n = 432) patients with ACC treated at MD Anderson, and controls (n = 1,204) were healthy and genetically unrelated spouses of patients at MD Anderson who had cancers not associated with smoking. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 11 , 16 Epidemiological risk factors for ACC are not well understood, although recent studies have identified an increased incidence in male cigarette smokers. 17 19 In females, estrogen exposure has been implicated as a risk factor due to an increased incidence of ACC in users of the oral contraceptive pill, 19 and the anti-proliferative effects of estrogen inhibition on ACC cells in vitro . 20 …”
Section: Epidemiologymentioning
confidence: 99%
“… 11 , 16 Epidemiological risk factors for ACC are not well understood, although recent studies have identified an increased incidence in male cigarette smokers. 17 19 In females, estrogen exposure has been implicated as a risk factor due to an increased incidence of ACC in users of the oral contraceptive pill, 19 and the anti-proliferative effects of estrogen inhibition on ACC cells in vitro . 20 …”
Section: Epidemiologymentioning
confidence: 99%
“…Adrenocortical carcinomas (ACCs) are rare cancers with 0.5-2 new cases per million diagnosed every year in the United States. 1,2 ACC is associated with a very poor prognosis. Complete surgical resection is the only curative therapeutic option but is possible in less than half of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In men, several studies ascertained that tobacco use increased the risk of adrenocortical carcinoma. [27][28][29][30] In women, increased risks were found in users of oral contraceptives, particularly those who used them before the age of 25 years. [27] Based on the results of trend analyses in our study, both sexes showed a similar upward trend in adrenocortical carcinoma incidence.…”
Section: Discussionmentioning
confidence: 99%